A critical study on female roles in television commercials of Bangladesh - Moriom Begum Mim; Maliha Tabassum (Informasi, 2021)
Media representation of female gender roles in advertising are relentlessly contested themes in a traditional society. Stereotypical representation not only limits the socially accepted traditional roles of gender, but also has an impact on how people perceive women. This study has focused on how women characters are constructed in order to understand reflection of stereotypical gender norms in Bangladeshi television commercials. Stuart Hall’s representation theory has adapted as the framework for conceptualizing the context of this study and scrutinizing the data. Using qualitative and quantitative methods, this paper has explored how such representations constitute unequal gender identities, traditional norms and perpetuate subtle forms of colorism towards women. This study found that dominant patriarchal ideology is deeply embedded in television commercials of Bangladesh; there is a discrimination towards the construction of women's image. Moreover, such media representations generate the ideology of beauty in a negative way and push the concept of colorism towards women.